EPID-11. A MULTI-INSTITUTIONAL COMPARATIVE ANALYSIS OF THE CLINICAL, GENOMIC, AND SURVIVAL CHARACTERISTICS OF PEDIATRIC, YOUNG ADULT AND OLDER ADULT PATIENTS WITH IDH-MUTANT GLIOMA. (9th November 2020) - Jane Lim-Fat, Mary; Vogelzang, Jayne; Woodward, Eleanor; McGovern, Alana; Ma, Clement; Al-sayegh, Hasan; Alexandrescu, Sanda; Margol, Ashley; Cotter, Jennifer; Cole, Kristina; Li, Marilyn; Owens, Emily; et al.
Abstract: BACKGROUND: Prognostic significance of IDH -mutation in glioma is incompletely understood in children and adolescents/young adults (YAs). We compared the clinico-genomic features, outcomes and prognostic factors observed in IDH -mutant gliomas across age groups. METHODS: Clinical, histologic and molecular data of patients with IDH -mutant gliomas from 8 pediatric institutions (spanning twenty years) and adult patients from two institutions (from 2013–2019) were identified. Patients were grouped as pediatric (< 19y), YA (19y to < 40y) or older adult (≥ 40y). Genomic alterations, including somatic mutations and copy number variants, were captured with institutional next generation sequencing. Factors were compared across age categories using Fisher's exact test or analysis-of-variance. Cox proportional-hazards regression tested factors for association with overall (OS) and progression-free survival (PFS). RESULTS: Of 379 patients, 48(13%) were pediatric, 204(54%) YA and 127(33%) older adult. Histological subtype differed significantly by age group (p< 0.0001). YAs had higher rates of malignant transformation (p=0.01) and shorter time-from-diagnosis-to-malignant transformation (p=0.01) compared to other age groups. Analysis of genomic alterations revealed an age-related difference in distribution in ATRX mutations only (p=0.0018). Median PFS and OS for the entire cohort were 4.62 and 17.19 years. In univariate models, PFS differed by age group (p=0.0012), with YAs having the worst outcomes. Lack of MGMT methylation (p=0.024) predicted poorer OS. Upfront observant management was predictive of poorer PFS. Gene mutations were not associated with PFS. In multi-variable models, YAs had shorter PFS compared to pediatric (hazard ratio [HR]=2.03, p=0.01) and older adults (HR=1.59, p=0.003) after adjusting for histology, extent of resection, and initial therapy. Age at diagnosis was not associated with OS in multi-variable analysis. CONCLUSIONS: Within our cohort, YA with IDH -mutant tumors progressed more quickly compared to their pediatric counterparts. Further study of YA patients with IDH -mutant glioma is critical to better define best practices for this group.